2013
DOI: 10.14260/jemds/615
|View full text |Cite
|
Sign up to set email alerts
|

Age Changes in the Thymus- A Histological and Morphological Study

Abstract: A histological and morphological study of human thymus obtained from autopsy was done. A steady increase in weight of thymus till puberty and thereafter a steady decline was noted. Involution was by fatty infiltration after puberty. Hassall's corpuscles were seen in all the specimens and its size or shape had no relation to the age or involution of the gland. There was an increase in the number of Hassall's corpuscles till puberty after which a progressive decrease was observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…According to research by (Sivan et al, 2013), who also demonstrated that the stromal elements of mesodermal origin are capillaries, septa and perivascular spaces and single invasive cells.…”
Section: Discussionmentioning
confidence: 99%
“…According to research by (Sivan et al, 2013), who also demonstrated that the stromal elements of mesodermal origin are capillaries, septa and perivascular spaces and single invasive cells.…”
Section: Discussionmentioning
confidence: 99%